Analisis Efektivitas Dan Efisiensi Pengelolaan Dana Nagari (Studi Pada Nagari Di Kabupaten Agam) - Suci Febriyanti; Halmawati Halmawati (Universitas Negeri Padang, 2020)
The research aims to determine the effectiveness and efficiency of the management of nagari funds in Agam Regency in 2015-2018 and to find out the management of nagari funds in Agam Regency in accordance with Law Number 2014 concerning Villages and Minister of Home Affairs Regulation Number 113 years 2014 on Village Financial Management. This research is a descriptive quantitative research. Data collection techniques are questionnaires, documentation and literature study. Questionnaires were distributed to guardians of the village, village staff (village secretary, village treasurer and planning committee), chair of the BPD, deputy chair of the BPD, and members of the BPD (representing one of the members) in 17 (seventeen) villages. The results of this study prove that (1) the effectiveness of 17 (seventeen) nagari can be concluded to be effective. While the efficient level of 17 (seventeen) nagari can be concluded to be still inefficient. (2) the results of the validity and reliability test show that overall the statement items used in the questionnaire showed very good results, meaning that the management of the nagari funds in Agam Regency was in accordance with Law Number 2014 concerning Villages and Minister of Domestic Affairs Number 113 of 2014 concerning Village Financial Management.